2000
DOI: 10.1054/bjoc.1999.1171
|View full text |Cite
|
Sign up to set email alerts
|

True

Abstract: Summary Molecular charge is one of the main determinants of transvascular transport. There are, however, no data available on the effect of molecular charge on microvascular permeability of macromolecules in solid tumours. To this end, we measured tumour microvascular permeability to different proteins having similar size but different charge. Measurements were performed in the human colon adenocarcinoma LS174T transplanted in transparent dorsal skinfold chambers in severe combined immunodeficient (SCID) mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(41 citation statements)
references
References 42 publications
1
40
0
Order By: Relevance
“…When measuring the tumor uptake of a compound, the distinction between extravasated material in the vicinity of the vessels and the material which is taken up by tumor endothelial cells in the neovasculature is difficult. Some researchers describe enhanced interactions with endothelial cells, for example by cationic charges (see section1.3.2), as an increase in the effective P of the vessel [53, 54]; others consider these interactions to be the product of absorption and endocytosis by the endothelium [55, 56]. The black box accounts, among other things, for that uncertainty on the effective concentration in the vasculature available for extravasation ( i.e.…”
Section: Passive Targeting: Nearly 30 Years Of the Epr Effect…mentioning
confidence: 99%
See 1 more Smart Citation
“…When measuring the tumor uptake of a compound, the distinction between extravasated material in the vicinity of the vessels and the material which is taken up by tumor endothelial cells in the neovasculature is difficult. Some researchers describe enhanced interactions with endothelial cells, for example by cationic charges (see section1.3.2), as an increase in the effective P of the vessel [53, 54]; others consider these interactions to be the product of absorption and endocytosis by the endothelium [55, 56]. The black box accounts, among other things, for that uncertainty on the effective concentration in the vasculature available for extravasation ( i.e.…”
Section: Passive Targeting: Nearly 30 Years Of the Epr Effect…mentioning
confidence: 99%
“…Once again, it is usually difficult to address both phenomenon independently [54]. The presence of surface charge can alter the opsonisation profile of the material, its recognition by cells in the organs of the MPS and its overall plasma circulation profile (↓ C v ) [11, 12, 86-92].…”
Section: Passive Targeting: Nearly 30 Years Of the Epr Effect…mentioning
confidence: 99%
“…Cationic nanoparticles may penetrate tumours more than neutral or anionic particles 44 as a result of attractive electrostatic forces between cationic particles and anionic endothelial glycocalyx 45 . Yet neutral or anionic particles distribute throughout tumours more effectively than cationic particles 46 because of minimized binding to anionic matrix molecules 28 .…”
Section: Tailoring Materials To Specific Tumoursmentioning
confidence: 99%
“…Notice, that because these particles travel with the velocity of the fluid, some of them might not bind to the vessel wall and go through the wall openings into the tumor interstitial space. Indeed, experimental and theoretical studies have shown that cationic nanoparticles have superior transvascular flux compared to their anionic or neutral counterparts 69,7478 . Furthermore, studies using zwitterionic quantum dot particles have shown that the spatial configuration of the surface charge plays also a role in the amount of the particles that crosses the vessel wall 79 .…”
Section: Design Considerationsmentioning
confidence: 99%